Factors Influencing the Effect of Race on Established Periodontitis Prevalence - Luisa N. Borrell, DDS, PhD, MPH; Brian A. Burt, BDS, MPH, PhD; Brenda W. Gillespie, MS, PhD; (Blackwell Synergy, 2003)
This paper identifies differences in prevalence of established periodontitis and evaluates factors that might explain the differences between non- Hispanic African Americans ( ~ 2 3 2a)n d whites (n= 199) in the Detroit tricounty area.